Pelatihan Dasar Investasi Saham di Pasar Modal Indonesia beserta Fintech Pendukungnya - Rini Indrayani; Yola Andesta Valenty (Universitas Muria Kudus, 2023)
The Covid-19 pandemic that has spread to Indonesia since the beginning of 2020 has dramatically affected various sectors of human life. One of the sectors most affected is the economic sector. Difficult economic conditions increase public awareness of the importance of owning investments. One type of investment widely looked at by the public is a stock investment in the Indonesian Capital Market. Various supporting application services and educational content related to stock investment also continue to increase production. One rapidly growing service is Fintech (Financial Technology), which can be used as an investment medium. However, because so many options are available, people have difficulty choosing suitable media and tools. A few people are even ensnared by “bogus investments” due to a lack of understanding regarding investments that comply with OJK (Financial Services Authority) regulations.Therefore, education about stock investment needs to be supported by understanding various safe options and can be an option for investing. Therefore, it is necessary to carry out community service activities related to basic training on stock investment in the Indonesian capital market along with supporting fintech supervised by the OJK. The output of this activity is training services to increase public knowledge about the importance of investment and fintech options that can be used to invest safely.